Black Queer Activism During the Aids Epidemic - Donovan Wright, (The Toro Historical Review, 2022)
The history of LGBTQ Americans has frequently been told through the lens of White Queer individuals , and most Black American historiography fails to acknowledge the contributions that Black Queer Americans have made to end racial discrimination. Several publications throughout the 1980s demonstrate the efforts that Black Queer Americans have made in the fight against racism and homophobia that plagued the United States.